2014
DOI: 10.1371/journal.pone.0107930
|View full text |Cite
|
Sign up to set email alerts
|

Customized Reference Ranges for Laboratory Values Decrease False Positive Alerts in Intensive Care Unit Patients

Abstract: BackgroundTraditional electronic medical record (EMR) interfaces mark laboratory tests as abnormal based on standard reference ranges derived from healthy, middle-aged adults. This yields many false positive alerts with subsequent alert-fatigue when applied to complex populations like hospitalized, critically ill patients. Novel EMR interfaces using adjusted reference ranges customized for specific patient populations may ameliorate this problem.ObjectiveTo compare accuracy of abnormal laboratory value indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Therefore, the reference interval is an approximation of what can be expected in the population. This difficulty has been recognised in critical care medicine leading to calls for the development of a new normative data base for the critically ill 4…”
Section: But What Is Meant By ‘Normal’?mentioning
confidence: 99%
“…Therefore, the reference interval is an approximation of what can be expected in the population. This difficulty has been recognised in critical care medicine leading to calls for the development of a new normative data base for the critically ill 4…”
Section: But What Is Meant By ‘Normal’?mentioning
confidence: 99%
“…Another type of alert geared to detection are abnormal laboratory value alerts with thresholds that exceed the recommended laboratory limit or higher. Alert thresholds with abnormal values higher than acceptable are often targeted at high specificity and low sensitivity, thus possibly reducing alert fatigue but limiting the value in ADE prevention[40]. Still antidote alerts and alerts set with a high abnormal laboratory value thresholds can be useful in understanding the environment, providing an opportunity to assess for causal factors and preventing future events through systematic changes[37].…”
Section: Detection Of Me and Ades Using Cdsmentioning
confidence: 99%
“…Brought to you by | Ghent University Library Authenticated Download Date | 12/14/18 11:38 PM standard RIs may not be a reliable tool in assessing critically ill patients because many patients still have derangements upon the discharge from the ICU. In fact, it has previously been shown that adjusted RIs for the ICU population decrease false-positive results and increase true-negative results [13]. Many laboratory derangements do not endanger the ICU patient, do not necessitate further intervention and should not preclude discharge from the ICU.…”
Section: Discussionmentioning
confidence: 99%